Rozwiaz rownanie korzystajac z rozkladu na czynniki √3x=-3x^2 Rozwiaz rownanie: 5-x^2=x^2+3 x^2=(1-x)(1+x) (2x+3)^2=(x-3)^2

Rozwiaz rownanie korzystajac z rozkladu na czynniki √3x=-3x^2 Rozwiaz rownanie: 5-x^2=x^2+3 x^2=(1-x)(1+x) (2x+3)^2=(x-3)^2
Odpowiedź
Martini151

√3x=-3x^2  √3x+3x^2 = 0  x( √3 +3x ) = 0  x =0 v  √3 +3x =0            3x = - √3              x = (- √3)/3  5-x^2=x^2+3  -2x^2 +2 =0  -2x^2 = -2   x^2 = 1   x = 1 v x = -1  x^2=(1-x)(1+x)  x^2 = 1 - x^2  2x^2 = 1  x^2 = 1/2  x = 1/√2  v x = -1/√2  (2x+3)^2=(x-3)^2  4x^2 + 12x +9 = x^2 - 6x + 9  3x^2 + 18x =0  3x( x^2 + 6)= 0  3x =0     x^2 +6 =0  x =0       x^2 = -6                 spr. 

Dodaj swoją odpowiedź